2007
DOI: 10.2106/jbjs.f.01102
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis Associated with Osteomyelitis in Children

Abstract: Deep venous thrombosis in association with musculoskeletal infection is more common in children over the age of eight years who have osteomyelitis caused by methicillin-resistant Staphylococcus aureus and who present with a C-reactive protein level of >6 mg/dL. Diagnostic venous imaging studies should be performed to assess for the presence of deep venous thrombosis in children with osteomyelitis, especially those who have these risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 4 publications
2
57
0
1
Order By: Relevance
“…With the emergence of CA-MRSA, deep venous thrombosis (DVT) adjacent to the site of OM has been described by several groups (506)(507)(508)(509)(510). DVT with acute OM has been associated with MRSA (506, 508), PVL-positive strains of S. aureus (510), and USA300 in particular (507).…”
Section: Osteoarticular Infections In Childrenmentioning
confidence: 99%
“…With the emergence of CA-MRSA, deep venous thrombosis (DVT) adjacent to the site of OM has been described by several groups (506)(507)(508)(509)(510). DVT with acute OM has been associated with MRSA (506, 508), PVL-positive strains of S. aureus (510), and USA300 in particular (507).…”
Section: Osteoarticular Infections In Childrenmentioning
confidence: 99%
“…In a recent series, subperiosteal abscesses only occurred in children with a CRP greater than 3.6 mg/dL. Children with MRSA infection and a CRP greater than 6 mg/dL have a 40% chance of having deep venous thrombosis [11,12].…”
Section: Clinical Considerationsmentioning
confidence: 97%
“…Surgery is likewise more likely to be required for abscess drainage in these patients (Hollmig et al, 2007, Bouchoucha et al, 2010). …”
Section: Venous Thromboembolismmentioning
confidence: 99%
“…Isolated case reports of using other antibiotics such as daptomycin effectively have also been published (Erturan et al, 2012). duration of follow up after discharge from hospital is not established, however, one study reported that thrombus resolved after a mean of 11 weeks (Hollmig et al, 2007). From the authors' previous experience with this condition, serial MRI scans were invaluable in assessing disease progression and identifying late complications e.g.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation